Comparison of the long-term efficacy and safety of generic Tacrobell with original tacrolimus (Prograf) in kidney transplant recipients - Son SY; Jang HR; Lee JE; Yoo H; Kim K; Park JB; Kim SJ; Oh HY; Huh W (Dove Medical Press, 2017)
Seung Yeon Son,1 Hye Ryoun Jang,1 Jung Eun Lee,1 Heejin Yoo,2 Kyunga Kim,2,3 Jae Berm Park,4 Sung Joo Kim,4 Ha Young Oh,1 Wooseong Huh1 1Department of Medicine, Samsung Medical Center, Sungkyunkwan University School of Medicine, 2Statistics and Data Center, Research Institute for Future Medicine, Samsung Medical Center, 3Department of Digital Health, SAIHST, 4Department of Surgery, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Republic of Korea Abstract: This study aimed to evaluate the long-term efficacy and safety of a generic tacrolimus (Tacrobell [TCB]) compared to the original tacrolimus (Prograf [PGF]) in kidney transplant recipients. In this retrospective observational study, we analyzed the data from 444 patients who took TCB as a first-line immunosuppressive drug and 245 patients who took PGF. The 5-year graft survival rate was 92% for patients in the PGF group and 97% for patients in the TCB group, respectively. Cox proportional hazards for a one-sided, noninferiority model showed noninferiority (upper confidence interval [CI] limit of the hazard ratio [HR]<1.2) for TCB compared to PGF (HR: 0.58; 95% CI: 0–1.14). The 5-year patient survival rate was 96% for patients in the PGF group and 97% for patients in the TCB group. Cox proportional hazards for a one-sided, noninferiority model showed noninferiority (upper confidence interval limit of the HR<2.0) for TCB compared to PGF (HR: 0.83; 95% CI: 0–1.95). The 5-year acute rejection-free graft survival rate was not significantly different between the groups (TCB 67%, PGF 68.8%; P=0.6286). The incidence of adverse events including adverse cardiovascular or cerebrovascular events, malignancies, new-onset diabetes after transplantation, and infection events did not differ significantly between the two groups. We conclude that TCB is a comparable alternative to the original tacrolimus as a first-line immunosuppressive drug. Producers of generics should support further study of their products after approval to assure physicians of their efficacy and safety. Keywords: kidney transplant, generic, tacrolimus